Prescription to over-the-counter switches in the United States - Jongwha Chang; Allison Lizer; Isha Patel; Deepak Bhatia; Xi Tan; Rajesh Balkrishnan (Wolters Kluwer Medknow Publications, 2016)
As the role of the pharmacist becomes more patient and counseling-centered, the healthcare market is changing to keep pace with more modern needs, such as self-treatment. Self-treatment provides patients the ability to diagnose their own condition and pick an appropriate medication from the pharmacy to treat their symptoms. This process allows a certain freedom for consumers to actively engage in their own health. In order for patients to self-treat, access to over-the-counter (OTC) medication is of prime importance. Many medications that are available as OTC today were previously labeled as prescription medications. As more safety studies and trials are conducted for different drugs, they can be deemed appropriate for use without a prescription. This review study discusses the process of switching of prescription medications to OTC medications in the United States and the implications of switching on patients, practitioners, drug makers, and insurers.